ADVERTISING COPYWRITING OF BATIK SEMARANG ON INSTAGRAM @BATIKSEMARANG16 - Lenny Setyowati (Jurnal Komunikasi dan Media, 2022)
Internet has helped marketers to reach larger markets, potential consumers at any time or place. With the change in advertising activities, and the advent of social media has moved marketers from conventional media to social media, because advertising costs are far cheaper and measurable. Instagram is used by marketers to promote its products, including batik. The study is focused on the elements of copywriting, the types of copywriting applied to the social media of instagram @batiksemarang16. The study is qualitative approaches and descriptive methods. The data collection technique used are observation, a documentary of content content where there are elements of copywriting, a type of copywriting from instagram @batiksemarang16 and archive studies. Hopefully, the results of this study will become a reference to a copywriting in the process of advertising in social media. From the 35 of the content of @batiksemarang16 account has used the suggested elements in good copywriting sucah as headlines, sub-headlines, slogans, body copy and taglines. What's interesting is that all of the contents used a body copy element. It was found a combination of copywriting elements to make content more creative and for add value to the copywriting. There were types of copywriting and the number of instagram accounts @batiksemarangang16. From 13 types of copywriting unfound content that used types competitive copy dan imagination copy.